# Aim: How do we solve quadratic equations by completing square?

## Presentation on theme: "Aim: How do we solve quadratic equations by completing square?"— Presentation transcript:

Aim: How do we solve quadratic equations by completing square?
Do Now: 1. factor: (x – 2)2 is called perfect square 2. Solve for x: (x – 7)(x + 1) = 0, x = 7, –1 3. Solve for x:

Unlike # 2, Do Now #3, the trinomial is not factorable, therefore, we cannot solve it by factoring. A special method is needed to solve this type of equation. The method we use is called completing square. Move the constant to the right Find the square of half the middle term Both sides of the equation add the square of half middle term (x – 3)2 = 2 Factor to complete the square for the left side Take square root on both sides

Example : x2 + 6x + 2 = 0 x2 + 6x + ___= -2+___ x2 + 6x + 9 = -2 + 9
Move the constant. x2 + 6x + ___= -2+___ Form a “perfect square”. x2 + 6x + 9 = Factor & Simplify. (x + 3)2 = 7 (x + 3)2 = 7 Square root. x + 3 = ± 7 x = -3 ± 7 Solve what is left.

x2 + 4x - = 0 + + 3 2 3 2 Solve for x: 2x2 +8x - 3 = 0 2 2 2
Each term divided by the leading coefficient 2 2 2 x2 + 4x - = 0 3 2 Move the constant to the right side. 3 2 + + Add the square of the middle term on both sides

Factor left side and simplify right side
Take square root on both sides solve for x

Solve for x by completing square
1. x2 + 6x + 3 = 0 2. x2 – 4x – 6 = 0 3. x2 + 10x + 17 = 0

Similar presentations